2005
DOI: 10.1007/s10584-005-6776-4
|View full text |Cite
|
Sign up to set email alerts
|

Future Effects of Ozone on Carbon Sequestration and Climate Change Policy Using a Global Biogeochemical Model

Abstract: Exposure of plants to ozone inhibits photosynthesis and therefore reduces vegetation production and carbon sequestration. The reduced carbon storage would then require further reductions in fossil fuel emissions to meet a given CO 2 concentration target, thereby increasing the cost of meeting the target. Simulations with the Terrestrial Ecosystem Model (TEM) for the historical period show the largest damages occur in the Southeast and Midwestern regions of the United States, eastern Europe, and eastern China.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
170
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(182 citation statements)
references
References 44 publications
6
170
3
Order By: Relevance
“…This enhanced IGSM model is nevertheless computationally efficient enough to be used in sensitivity and uncertainty studies with the IGSM (21). In addition, versions that partly couple a 3D atmospheric circulation and chemistry model into the IGSM framework are applied to specific issues (e.g., 22).…”
Section: Integrated Global System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This enhanced IGSM model is nevertheless computationally efficient enough to be used in sensitivity and uncertainty studies with the IGSM (21). In addition, versions that partly couple a 3D atmospheric circulation and chemistry model into the IGSM framework are applied to specific issues (e.g., 22).…”
Section: Integrated Global System Modelmentioning
confidence: 99%
“…The use of a mosaic scheme within each grid enables a simulation of multiple vegetation types without the need for a very fine-grid resolution. The land model employs three coupled submodels to represent the terrestrial water, energy, and ecosystem processes: the community land model (27) calculates the water and energy balances, including the roles of plants; the terrestrial ecosystems model (TEM) (22,28,29) simulates the carbon and nitrogen cycles in vegetation and soils; and the natural emissions model (6) embedded within the TEM simulates the natural emissions of CH 4 and N 2 O, taking into account climate and ecosystem processes in wetlands and soils around the world.…”
Section: Integrated Global System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a reduction in the net primary production (NPP) ranging from 3% to 16%. Felzer et al (2004Felzer et al ( , 2005 incorporated the algorithms from Reich (1987) and Ollinger et al (1997) for hardwoods, conifers, and crops into a biogeochemical model. Their study across the US indicated a 2.6-6.8% mean reduction in the annual NPP during the late 1980s and early 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…The model takes into consideration how land carbon dynamics are influenced by multiple environmental factors, both static ones such as soil texture and elevation, and dynamic ones such as CO 2 fertilization, climate change and variability, land-use change, and ozone pollution (Melillo et al 1993(Melillo et al , 2009McGuire et al 2001;Tian et al 2003;Felzer et al 2005). In this study, carbon dynamics are simulated for a mosaic of land-cover cohorts contained within each 0.5°latitude by 0.5°longitude grid cell.…”
Section: The Terrestrial Ecosystem Model (Tem)mentioning
confidence: 99%